Chill to Thrill: How Ice-breaking Transforms TOEFL Preparation and Student Engagement - Leba, Wilhelmina Eryuni; Ardhy, Andi Anugrah Surya (Journal of English Language Teaching, Linguistics, and Literature Studies, 2024)
This research explores students' roles and perceptions towards ice-breaking activities in the context of TOEFL preparation classes at one of the universities in East Java. The research employed a qualitative approach with data analysis conducted using NVivo 12. The study involved 20 TOEFL preparation class students who actively participated in ice-breaking activities. The research instruments used were observation and semi-structured interviews to collect data on student perceptions of ice-breaking. Data analysis was carried out by identifying thought patterns that emerged from student responses to the ice-breaking activity. The research results show that ice-breaking activities effectively create a livelier and more interactive classroom atmosphere, increase students' active participation, and reduce anxiety often experienced when preparing for the TOEFL test. In addition, the active role of mentors in facilitating these activities has proven to be very important in creating a supportive and inclusive learning environment. In-depth observations also revealed that ice-breaking strengthens social interaction and collaboration between students, increasing their understanding of the material being taught. Future researchers should explore the long-term impact of ice-breaking on students' academic performance in the TOEFL test.Keywords: Ice-breaking, Student perception, TOEFL preparation